Analysing tertiary students’ reading proficiency of CEFR aligned texts via online discussion forum in a learning management system - Ruhil Amal, Azmuddin; Ainul Azmin, Md Zamin; Hamizah, Zahari; Rahmah, Mokhtar; Fatin Aliana, Mohd Radzi; Daing Nafiz, Idris (UiTM Press, 2023)
Learning has taken a new dimension for students in higher institutions because they are now required to read large amounts of online materials constantly for academic purposes. Despite the use of technology, students are unable to take advantage of its full potential to read effectively online. This study investigated ESL learners’ use of Online Discussion Forums (ODFs) in a Learning Management System (LMS) to aid reading of texts aligned within Common European Framework of Reference for Languages (CEFR). This study employed a mixed method approach of collecting data within the context of a 14-week semester. Data collection consists of pre and post-tests as well as ODF threads from 55 ESL students enrolled in various courses at the university. Descriptive and content analyses were performed using SPSS and NVivo programs, respectively. Content analysis was confirmed using Cohen Kappa analysis that gave an almost perfect score, suggesting that the findings were reliable. Data analysis on online discussion threads confirms that students can achieve higher level conversations and discuss ideas to achieve comprehension. Post-test scores reveal ODF's interactive heuristic approach to learning has enhanced learners' ability to comprehend online materials. This becomes significant for instructors and program developers to integrate materials selection as well as relevant ODF topics to maximize learning potential.